2017
DOI: 10.1016/j.bbmt.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy for Symptom Management After Autologous Stem Cell Transplantation: Results From a Randomized Study

Abstract: High-dose chemotherapy followed by autologous stem cell transplantation (ASCT) is frequently performed in patients with hematologic malignancies. ASCT can result in significant nausea, pain, and discomfort. Supportive care has improved, and pharmacologic therapies are frequently used, but with limitations. Music has been demonstrated to improve nausea and pain in patients undergoing chemotherapy, but little data are available regarding the effects of music therapy in the transplantation setting. In a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 8 publications
1
51
0
3
Order By: Relevance
“…In one study with two song-based music therapy sessions per week, greater improvements in mood, but no differences in self-rated pain were observed in comparison with the control group (Dóro et al, 2017). In another trial using non-standardized interventions, patients receiving two music therapy sessions required less pain medication even though the subjective pain reduction was similar in music therapy and the control group (Bates et al, 2017). The reduction in analgesics intake was also found in a similar study, where stem cell transplantation patients additionally reported a short-term reduction of subjective pain perception (Tuinmann et al, 2017).…”
Section: Music Therapy During Surgery and Transplantationmentioning
confidence: 99%
“…In one study with two song-based music therapy sessions per week, greater improvements in mood, but no differences in self-rated pain were observed in comparison with the control group (Dóro et al, 2017). In another trial using non-standardized interventions, patients receiving two music therapy sessions required less pain medication even though the subjective pain reduction was similar in music therapy and the control group (Bates et al, 2017). The reduction in analgesics intake was also found in a similar study, where stem cell transplantation patients additionally reported a short-term reduction of subjective pain perception (Tuinmann et al, 2017).…”
Section: Music Therapy During Surgery and Transplantationmentioning
confidence: 99%
“…The programme had a positive short‐term effect on diarrhoea ( p = 0.014) but no effect at all on nausea (Jarden, Baadsgaard, Hovgaard, Boesen, & Adamsen, 2009). One study investigated the impact of music therapy on nausea and found a significant difference with regard to the nausea score in favour of the control group after 7 days ( p = 0.035), but no differences were observed at other time points (after 1 and 5 days) (Bates et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Music therapy significantly reduced anxiety and helped to improve both the mood and subjective assessment of life quality of cancer patients preparing for radiotherapy treatment or undergoing it (Rossetti et al, 2017). It can also be a reasonable non-pharmacological method of coping with pain in the case of patients undergoing bone marrow transplantation: patients whose treatment included music therapy proved to need significantly lower doses of pain medication (Bates et al, 2017). These data are in agreement with recent results that showed a significant improvement in treatment, and increased survival, accompanied by reduction in cortisol and the telomere length, in patients with tumours, who actively participated in a long-term program of supportive psychotherapy adjusted for individual patterns (Carlson et al, 2015;.…”
Section: Discussionmentioning
confidence: 99%